Exercising with a denervated heart after cardiac transplantation - Mettauer, Bertrand; Levy, François; Richard, Ruddy; Roth, Olivier; Zoll, Joffrey; Lampert, Eliane; Lonsdorfer, Jean; Geny, Bernard (Annals of transplantation, 2005)
Heart transplantation (HTR) is now an accepted life-extending procedure for those dying of intractable heart failure (CHF). HTR patients expect a high quality of life which implies a reasonable exercise capacity. Nevertheless HTR present unique exercise challenges with both central and peripheral factors of limitation that result in peak oxygen uptakes of 60-70% of age-matched normal subjects. Among central factors persistent chronotropic incompetence questions the occurrence and role of the graft reinnervation. Among peripheral factors the energetic impairement of the skeletal muscle seem to result more from microvascular abnormalities than from an actual deficit in oxidative capacity, questioning the mechanism of recovery from the CHF peripheral myopathy and the role of immunosuppressive drugs. Endurance and resistance training programs may reverse at least in part most but not all of these abnormalities. Training permits patients to engage in sports and even to participate in competitive events that are rewarding to them but also to the community because it promotes organ donation and confidence in medical achievements. Mechanisms of exercise impairments and improvements resulting from training are discussed in the perspective of current literature. Areas of future research and recommendations for the practice of sports after HTR are suggested.